Can Multiple Forms of Undernutrition Among Children and Women Be Tackled Efficiently? A Case of Shared Determinants (P11-124-19). (13th June 2019) - Avula, Rasmi; Nguyen, Phuong; Pramanik, Priyanjana; Tran, Lan; Sr., Marie Ruel,; Menon, Purnima
Abstract: Objectives: Globally, it is recognized that multiple forms of undernutrition exist. Yet, little evidence exists on co-existence of multiple forms of undernutrition or on the potential shared determinants of these manifestations. Therefore, using data from India, we aimed to: 1) estimate the co-occurrence of undernutrition among children (stunting and anemia) and women (underweight and anemia); and 2) identify their shared determinants. Methods: We used National Family Health Survey data from 2016 (n = 126, 338 children 6–59 mo; 159, 752 women). We examined co-occurrence of stunting and anemia among children and underweight and anemia among women, comparing observed versus expected frequencies using chi-square tests. We used multivariate logistic regression models to study associations between nutrition outcomes and determinants (household, maternal and child-level), and identified determinants that were shared across the outcomes. Results: The observed co-occurrence of stunting and anemia among children was 25% and of underweight and anemia among women was 15%. Observed frequencies were significantly greater than expected frequencies for all comparisons ( P  < 0.0001). Women's education (OR: 0.60 to 0.84), wealth status (OR: 0.56 to 0.81) and improved sanitation (OR: 0.74 to 0.94) were protective against all forms of undernutrition. Care during pregnancy was protective against stunting (OR = 0.83; P  < 0.001) and anemia (OR = 0.94; P  < 0.001) among children and underweight (OR = 0.88; P  < 0.001) among women. Maternal underweight (OR = 1.31; P  < 0.001) and anemia (OR = 1.09; P  < 0.001) were risk factors for child undernutrition. Conclusions: Co-occurrence of undernutrition is prevalent among women and children in India. Multiple forms of undernutrition also share similar determinants. Investing in reducing poverty, improving education, sanitation, and use of antenatal care could address multiple forms of undernutrition, thus ensuring more efficient use of resources. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by International Food Policy Research Institute.